Carrier-envelope offset frequency measurement by means of an external optical resonator - Giannotti, Dario; Suerra, Edoardo; Canella, Francesco; Cialdi, Simone; Laporta, Paolo; Galzerano, Gianluca (Frontiers in Physics, 2023)
A general-purpose method based on the implementation of the asymmetric Pound–Drever–Hall (PDH) technique is proposed to measure the carrier-envelope offset (CEO) frequency of a mode-locked laser using an external optical cavity. By analyzing the synchronously demodulated signal of the spectrally filtered cavity reflection when the optical resonator is locked to the mode-locked laser, a discriminating signal depending on the relative frequency offset between the mode-locked and optical cavity comb-like spectra is obtained. For a given geometry and group delay dispersion (GDD) of the cavity parameters (i.e., a known cavity mode offset), this signal can be used to retrieve the laser CEO. This approach turns out to be advantageous in terms of setup complexity with respect to other well-known techniques that rely on non-linear frequency generation, such as f–2f interferometers. In addition, this method can be used to precisely determine the laser–cavity spectral coupling, which is an important topic in cavity-enhanced spectroscopy and non-linear optics applications. After the theoretical description of the generalized asymmetric PDH signal, an experimental validation of the proposed method is reported using an Er-doped fiber frequency comb source centered at 1,550 nm, with a repetition rate of 250 MHz, locked to a linear optical cavity with a 1 GHz free spectral range. The theoretical effect of the GDD is confirmed experimentally using different cavity configurations. Moreover, the comparison with the CEO frequency values measured using an f–2f interferometer demonstrates the feasibility of the proposed method.